The Status of Diversity of Coral Reefs and Reef Fish Supporting Marine Tourism on Kodingareng Keke Island, Makassar City - Daris, Lukman; Massiseng, Andi Nur Apung; Jaya, Jaya; Wahyuti, Wahyuti; Zaenab, St (Hasanuddin University, 2023)
This study aimed to determine the potential diversity of the coral reef and coral reef fish ecosystems of Kodingareng Keke Island and the development strategies and priorities of Kodingareng Keke Island as a marine tourism destination. This research used purposive sampling with 50 respondents. The coral data collection method was Line Intercept Transect (LIT), with a transect line length of 50 meters and depth of 5 meters. The process used to obtain coral reef fish data was the Underwater Visual Census (UVC). The analysis showed that the average coral ranged from 63,6% to 77,8%. The average abundance of fish at 3 observation stations, namely Station I (17,65%), station II (14,78%) and Station III (18,67%), thus it can be concluded that this location is feasible for snorkelling and diving tourism. The priority programs for the development of the marine tourism area of Kodingareng Keke Island include increasing supervision, creating periodical Object Development Master Plans (RIPO), implementing local regulations on the use of coastal resources, involving local communities, the general public and the government in nature conservation activities, setting labour standards and improving the quality of local human resources through training.